Penerapan Asas Ultra Petitum Partium di Pengadian Agama Perspektif Hukum Islam - Rommy Hardyansah; Asis, Larasati Fitriani (Sekolah Tinggi Agama Islam Taruna Surabaya, 2024)
This research examines the application of the ultra petita partium principle in the Religious Courts from the perspective of Islamic law, namely a principle that prohibits judges from deciding cases beyond what is demanded by the parties to the case. This principle is one of the important principles held in religious justice. This research is based on legal research with the category of library research. The approach used in this research is a normative juridical approach. The results of the research show that basically the principles of justice, equality and non-burdensomeness in Islamic law are closely related to the application of the principle of ultra petitum partium. By ensuring that every individual is treated equally and that no decision exceeds the demands submitted, the Religious Courts can maintain fairness and integrity in every decision they make. However, there are exceptions where judges are deemed not to have violated the principle of ultra petitum partium when proceeding in the Religious Courts, especially in divorce cases regarding determining the maintenance of the wife and children who must be borne by the husband during the divorce lawsuit as stated in the provisional decision. Even without a provisional decision from the wife, the judge can issue a provisional decision.